An Analysis of the Provisions of Indian Labour Laws Pertaining to Women and their Implementation (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The gender-specific provisions of Indian labour laws are examined in depth in this article, and the article also evaluates the degree to which these sections are effectively implemented in various sectors of the economy. A robust structure has been established in India with the purpose of advancing gender equality and protecting the rights of women in the workplace. There are statutes such as the Equal Remuneration Act and the Maternity Benefit Act, as well as more contemporary employment regulations, that are included in this framework. However, women continue to face significant impediments in the form of legal and institutional barriers. The study has shed light on a number of significant challenges, some of which include the absence of legislative protections for women who are employed in informal sectors, the slack enforcement of existing legislation, and the marginalisation of unpaid care employment. Additionally, the study investigates the effects of recent modifications to the labour code from the point of view of gender, notably focussing on how these modifications have an impact on wage equality, social security, and workplace safety inside the workplace. Through the use of legal texts, secondary data, and court precedents, the purpose of this research is to facilitate the creation of Indian labour laws that are more inclusive, effective, and attentive to the realities of women workers. In doing so, it draws attention to significant gaps between the policy purpose and actual practice and offers potential remedies.